Stimulation of Deprivation Cycles with Spirulina platensis Feed Supplementation on Osphronemus gouramy Physiological Responses - Sorta Basar Ida Simanjuntak; Eko Setio Wibowo; Indarmawan Indarmawan (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2016)
Spirulina platensis is a phytoplankton, the cell wall composed of complex sugars so easily digested by fish. The present study was carried out to investigate stimulation cycle of feed deprivation with feed supplemented S. platensis the best to increase growth, hematological and body composition of gurami (Osphronemus gouramy). Groups of 24 fish, each in triplicate, were exposed to four different treatment for a period of 56 days. Sample measurements of growth done every 14 days, hematological and body composition measurements carried out at the end of the experiment. Growth was significantly different between stimulation cycle of feed deprivation and the control (P0.05). Conclusions result showed that stimulation cycles of feed deprivation could not improve growth and hematological, but could improve body composition. Feed deprivation is done to reduce the cost of production, high production costs due to high feed prices. During research on feed deprivation is done by giving commercial feed, this study is to provide feed supplementation S. platensis. Thus, the results of this study can be useful for science as S. platensis information can be used as a food supplement and and for the people cultivating gurami should be fed daily supplementation of S. platensis.How to CiteSimanjuntak, S. B. I., Wibowo, E. S. Indarmawan, I. (2016). Stimulation of Deprivation Cycles with Spirulina platensis Feed Supplementation on Osphronemus gouramy Physiological Responses. Biosaintifika: Journal of Biology Biology Education, 8(3), 378-385.